PeopleSmart : facilitator's guide - Silberman, Mel; Hansburg, Freda (San Francisco, CA : Pfeiffer, 2006)
Part of the PeopleSmart package, the People Quotient (PQ) Scale is designed to help your participants understand areas in which their people skills are weak or strong. This 40-item self-scoring inventory assesses participants on each of the program s skills: 1. Understanding people. 2. Expressing thoughts and feelings clearly. 3.
Facilitator's guide -- CD-ROM -- Participant workbook -- The people quotient (PQ) scale
Accompanying CD-ROM includes PowerPoint slides and video clips to accompany modules; links to additional resources; author information and contact information; additional help
Windows requirements: PC with MS Windows 98SE or higher.
Keywords: Interpersonal relations; Psychology, Industrial